2023
DOI: 10.1002/nop2.1939
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students' experiences of communication in a multilingual and multicultural clinical environment: A qualitative study

Daniel Opotamutale Ashipala,
Maujarukua Matundu

Abstract: AimThe aim of this study was to investigate nursing students' experiences of communication in a multilingual and multicultural clinical environment.BackgroundEffective communication in a healthcare setting plays a crucial role in patient care. Yet, since universities, globally, have experienced an increase in the enrolment of both local and international students in various degree programmes, student populations have become increasingly multilingual and multicultural. This study was conducted in a multilingual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…In the same vein, Moghaddam et al ( 2020 ) reported that nurses' lack of teaching skills is a barrier to student learning. In terms of language being a barrier to student learning, similar findings were reported in a study by Ashipala and Matundu ( 2023 ), who found that a poor command of the language of the clinical environment can result in unfavorable or unpleasant experiences and poor learning outcomes. This was also an issue highlighted by El Naggar and Almaeen ( 2020 ), who reported that language was an obstacle to the clinical teaching of nursing students.…”
Section: Discussionsupporting
confidence: 81%
“…In the same vein, Moghaddam et al ( 2020 ) reported that nurses' lack of teaching skills is a barrier to student learning. In terms of language being a barrier to student learning, similar findings were reported in a study by Ashipala and Matundu ( 2023 ), who found that a poor command of the language of the clinical environment can result in unfavorable or unpleasant experiences and poor learning outcomes. This was also an issue highlighted by El Naggar and Almaeen ( 2020 ), who reported that language was an obstacle to the clinical teaching of nursing students.…”
Section: Discussionsupporting
confidence: 81%
“…They are keenly aware of aging trends, noting that older adults are living longer due to improved healthcare services, socioeconomic factors, and advancements in technology. They emphasized the importance of management understanding the growing diversity among elderly individuals (Yava, 2023) and the need for staff to learn basic spoken languages to facilitate effective communication and mutual understanding in daily tasks (Ashipala & Matundu, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The diversity within healthcare teams is typically seen as beneficial for delivering high-quality care, but it can also place extra demands on culturally diverse patients and their primary caregivers, potentially impacting their overall well-being and the experiences of healthcare professionals (McCleskey & Cain, 2019;Burke et al, 2023;Ashipala & Matundu, 2023). Cultural competence is vital for delivering patient-centered care, which focuses on effective communication (Rassouli et al, 2020), personalized attention to individual needs, and respecting patients' rights.…”
Section: Discussionmentioning
confidence: 99%